Prospects of Women Empowerment Under The Pretext of Indonesia and Pakistan - Malik, Humera; Marwah, Sitti (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2021)
As many countries would benefit from promoting women empowerment, several developing countries are also endeavoring for it. Pakistan and Indonesia are among those countries who took serious measures to improve the state of women empowerment. This study provides the overview of the efforts of Indonesia and Pakistan made at state level to empower their women. This is the era when each country matches the rate of progress; opportunity would also come from raising the female participation. In both countries, hundred many women live their lives under the societal pressure which is being exerted by ancient traditions. The patriarchal structure swept up women to live as hand-maiden of men in society. In the result of multifaceted discrimination, women are lagging behind in many fields. The main theme of this research is to examine the level of women empowerment by focusing the arenas of politics, economic and social. This nature of this study is descriptive as well as exploratory. Qualitative method has been adopted to carry out this research. While conducting this research, both primary and secondary sources of data will be used. This study will be useful to identify the causes which detain the progress of women. This brief but comprehensive analysis will also help to recommend some suggestions to improve level of women empowerment in both states.